The witcher de Andrzej Sapkowski e a série da Netflix: adaptação literária para audiovisual ou narrativa em segundo grau- palimpsestos - Reato, Theodoro Silva [UNESP] (Universidade Estadual Paulista (Unesp), 2021)
This work aims to analyze the first episode of the audiovisual adaptation The Witcher (by Netflix) with the first volume of the literary work The Witcher by Andrzej Sapkowski. This research seeks to identify transformations, differences and similarities of the first episode entitled “The lesser evil” with the book - text of departure. It is observed that the adaptations of books to other media are not new, they are part of the history of cinema, television and comic books that have always used verbal literary texts as a basis for the construction of verbal-audiovisual narratives. For this reason, our aim is to investigate, demonstrate and compare the languages of verbal literary communication with an audiovisual that constitutes a central element of our work. We will use Gerard Genette's concept of Palimpsest as essential support for research on the topic that deals with the relationship between languages. Such an analysis is necessary to think about audiovisual narratives in the context of the 21st century, which are an instrument of a culture that, consequently, does not aim only at entertainment, but also at critically studying the production of content. Finally, we propose to reflect on the adaptation of literary texts for audiovisual media.

O presente trabalho tem como propósito analisar o primeiro episódio da adaptação audiovisual The Witcher (produzida pela Netflix) com o primeiro volume da obra literária The Witcher de Andrzej Sapkowski. Busca-se nesta pesquisa identificar as transformações, diferenças e semelhanças do primeiro episódio intitulado O mal menor com o livro - texto de partida. Observa-se que as adaptações de livros para outros meios não são novidades, fazem parte da história do cinema, televisão e histórias em quadrinhos que sempre usaram textos literários verbais como base para construção de narrativas verbo-audiovisuais. Por isso mesmo, o nosso objetivo é o de averiguar, demonstrar e comparar as linguagens da comunicação literária verbal com a audiovisual que se constitui em um elemento central de nosso trabalho. Utilizaremos o conceito de Palimpsesto de Gerard Genette como apoio essencial à pesquisa sobre o tema que trata das relações entre linguagens. Tal análise se mostra necessária para se pensar as narrativas audiovisuais no contexto do século XXI, que são um instrumento de uma cultura que, consequentemente, não visa só ao entretenimento, mas também a estudar criticamente a produção de conteúdo. Por fim, propomos fazer uma reflexão sobre a adaptação de textos literários para os meios audiovisuais.
Andrzej Sapkowski's the witcher and the Netflix series: literary adaptation for audiovisual or second-degree narrative - palimpsests
Keywords: Literary adaptation; Witcher; Palimpsest; Gerard Genett; Adaptação literária; Audiovisual; Palimpsesto